COMORBID DISORDERS IN CHRONIC MIGRAINE AND CHRONIC TENSION HEADACHES - Akhmedova Dilafruz Bahodirovna (Web of Journals Publishing, 2024)
Episodic forms of tension headaches are not considered as a major medical or social problem, while chronic tension headaches are accompanied by comorbid disorders, such as various depression, sleep disorders, somatoform disorders, in which the patient clearly distorts the functioning and quality of everyday life, the difficulty in choosing an effective treatment leads to chronic tension headaches to the level of a complex socio-medical problem.
Keywords: migraine, tension headache, chronic headache, comorbid disorder.